Desentralisasi dan Kesehatan Keuangan Daerah di Indonesia - Q.A., Dhea Tikha; Sujarwoto, Sujarwoto (Jurnal Ilmiah Administrasi Publik, 2015)
Local government fiscal health is important for effective fiscal decentralisation. This study examines local government fiscal decentralisation in Indonesia. Data comes from Indonesian Financial Information System 2013. The findings show that after more than four decades decentralisation, most of local governments are still strongly depend on central government in financing local development. The wide gap of fiscal capacity exists between local government at Java and outside Java. The findings suggest that improving local government capacity in mobilising and managing fiscal resources is vital to improve local government fiscal health in decentralised Indonesia.